THE PEDAGOGICAL ESSENCE OF LITERARY-SPEECH COMPETENCE IN PRIMARY SCHOOL READING LITERACY LESSONS (International journal of artificial intelligence, 2026)
This article analyzes the pedagogical essence of developing literary and speech competence in primary school reading literacy lessons. Literary-speech competence is considered as an important factor in shaping students’ ability to understand texts, express thoughts clearly, and develop critical and creative thinking skills. The study highlights the role of interactive methods, communicative approaches, and student-centered strategies in improving learners' reading comprehension and oral and written communication abilities. Special attention is given to the integration of modern pedagogical technologies and innovative teaching methods in enhancing pupils' language development. The findings show that systematic and purposeful instruction significantly increases students’ motivation, vocabulary enrichment, and overall communicative competence.